Togo : 2019 Article IV Consultation, Fourth Review under the Extended Credit Facility Arrangement, and Request for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2019)
Economic activity has been recovering, driven by robust performance in the export and agricultural sectors. Fiscal consolidation efforts have continued; Togo complied with the WAEMU deficit convergence criteria in 2017 and 2018, two years ahead of the timeline agreed by member states; public debt declined from 81 percent of GDP at end-2016 to 76 percent of GDP at end-2018. Inflation stood at 2 percent in March 2019 (y-o-y). The external position has improved. The privatization process for the first public bank encountered delays.